If Memory Serves : Gay Men, AIDS, and the Promise of the Queer Past - Castiglia, Christopher (Book collections on Project MUSE., 2012)
"The AIDS epidemic soured the memory of the sexual revolution and gay liberation of the 1970s, and prominent politicians, commentators, and academics instructed gay men to forget the sexual cultures of the 1970s in order to ensure a healthy future. But without memory there can be no future, argue Christopher Castiglia and Christopher Reed in this exploration of the struggle over gay memory that marked the decades following the onset of AIDS. Challenging many of the assumptions behind first-wave queer theory, If Memory Serves offers a new perspective on the emergence of contemporary queer culture"--Provided by publisher.